Pengaruh Alokasi Pajak Antar Periode dan Likuiditas Terhadap Kualitas Laba pada Perusahaan Pertambangan - Wastam Wahyu Hidayat (Sosio e-Kons, 2021)
This research aims to examine the effect of tax allocation between periods, and liquidity on earnings quality by proxying Discretionary Accruals. This study uses a quantitative approach. The population in this study were mining companies listed on the Indonesia Stock Exchange (IDX) during 2012 - 2017. The sampling method used was purposive sampling. Purposive sampling is a technique with certain considerations or that meets certain criteria so that the samples that can be taken in this study are 12 mining companies from a total population of 46 mining companies. Data analysis in this study used multiple linear regression analysis. In order to obtain unbiased test results, the classical assumption test is first carried out, then the model feasibility test is carried out. The results showed that partially at the 0.05 percent confidence level, the inter-period tax allocation variable partially had no effect on earnings quality with the DACC proxy because sig was greater than 0.05, i.e. 0.638. The liquidity variable partially has no significant effect on earnings quality because Sig is greater than 0.05 ie, 0.133, and Taken together, the Tax Allocation Variable between periods and Liquidity has no effect on Earnings Quality because Sig is greater than 0.05 ie, 0.319.